(untitled) (World Bulletin of Public Health, 2022)
In the article, the research conducted by M. Arifkhanova, U. Pratov, R. Shonazarov on annual plants and ephemeral plants distributed in the Fergana Valley is studied, analyzed and compared with the research conducted until now. Along with this, the article shows the geographical distribution of ephemeral plant species and their taxonomic changes from 1948 to the present 2022